Bullying in “Wonder” Movie: A Pragmatic Study (Journal of the College of Education for Women, 2024)
Bullying still occurs in the surroundings of teenagers. Those who have experienced bullying firsthand are often aware of its damaging effects. Bullying is the most common form of hostility that takes place in schools (Anderson, 2002:53). By applying Culpeper's (2011) Impoliteness, in bullying passages from the movie "Wonder," which is directed by Stephen Chbosky, the study intends to explain the most prevalent pragmatic strategies of impoliteness, the functions of impoliteness act, and responses towards impolite act. The purpose of this study is to examine the forms of bullying. The current study adopts a qualitative and quantitative method for analyzing five extracts by applying Culpeper's (2011) Impolitenessstrategies. They are analyzed into two levels; First, according to bullying behavior by Olweus’ definition of bullying behavior (1994), and second what are the pragmatic realizations of Impoliteness? Finding out that, according to the first level, there are three types of bullying behavior used in the movie, they are intention to harm, harmful outcome, and direct or indirect act. The second level includes: (1) Three types of impoliteness strategies (bald on record strategy, negative impoliteness, and off record politeness). (2) Limited functions as coercive function and entertaining function. (3) Specific responses are found in the movie. This study concludes that, according to Olweus (1994), bullying behavior can be defined into five essential components) Intention to harm, Harmful outcome, Direct or indirect acts, Repetition, and Unequal Power).